ANALISIS PERILAKU BELANJA ONLINE GENERASI Z STUDI KASUS PADA PENGGUNA TIKTOK DI KOTA BANDUNG - Haryati, Risna (Jurnal Ilmiah Magister Ilmu Administrasi, 2024)
This research aims to analyze how TikTok influences online shopping behavior among Generation Z, particularly in the city of Bandung. The main issue raised is how the interactive features and content offered by TikTok influence the purchasing decisions of Generation Z, which is increasingly dominating the digital market. This research also examines the factors that motivate and influence online shopping decisions, both rational and irrational. The research method used is a qualitative approach with a case study method. Data was collected through in-depth interviews with participants selected purposively based on specific criteria such as age (18-25 years), frequency of TikTok usage, and shopping experience through the platform. The data was then analyzed using thematic analysis methods to identify shopping behavior patterns and the influence of TikTok on consumer decisions. The research findings indicate that TikTok plays a significant role in influencing the shopping behavior of Generation Z in the city of Bandung. As many as 89% of respondents admitted to frequently making purchases after seeing products on TikTok, with the main motivations being special discounts (67%) and recommendations from influencers (15%). This finding underscores the importance of TikTok as an effective digital marketing platform, even though there are still challenges related to trust in influencer recommendations and consumer satisfaction.